2022
DOI: 10.1111/lam.13552
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Agrobacterium tumefaciens-mediated transformation conditions in Colletotrichum lindemuthianum: a step forward to unravel the functions of pathogenicity arsenals

Abstract: Significance and Impact of the Study: In the present study, we for the first time, report an efficient Agrobacterium tumefaciens-mediated transformation (ATMT) system for a hemibiotrophic fungus, Colletotrichum lindemuthianum. This optimized ATMT protocol is versatile and can be used for the functional genetic studies. Insertional mutagenesis studies produce thousands of mutant lines that need to be evaluated for pathogenicity loss and the traditional methods of pathogenicity assay in bean-anthracnose pathosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Hygromycin B is the most common selective marker used for filamentous fungal transformant screening. Previous studies reported that 200 μg mL −1 hygromycin B can completely inhibit the germination and growth of wild‐type Colletotrichum lindemuthianum race 2047 (Nabi et al., 2022), whereas 250 μg mL −1 hygromycin B can completely inhibit the growth of Colletotrichum acutatum isolate 397 (Talhinhas et al., 2008). This result indicates that the fungus is sensitive to hygromycin B.…”
Section: Discussionmentioning
confidence: 99%
“…Hygromycin B is the most common selective marker used for filamentous fungal transformant screening. Previous studies reported that 200 μg mL −1 hygromycin B can completely inhibit the germination and growth of wild‐type Colletotrichum lindemuthianum race 2047 (Nabi et al., 2022), whereas 250 μg mL −1 hygromycin B can completely inhibit the growth of Colletotrichum acutatum isolate 397 (Talhinhas et al., 2008). This result indicates that the fungus is sensitive to hygromycin B.…”
Section: Discussionmentioning
confidence: 99%